A novel roseosiphovirus infecting dinoroseobacter shibae DFL12T represents a new genus - Nana Wei; Longfei Lu; Yingying Li; Bo Ding; Lanlan Cai; Yunlan Yang (BMC Genomics)
Abstract Bacteria belonging to the Roseobacter clade are key players in marine ecosystems, contributing significantly to carbon and sulfur cycles. Marine viruses, particularly those targeting Roseobacter, play crucial roles in regulating microbial communities and biogeochemical processes. Despite their importance, phages infecting organisms of the Roseobacter clade remain poorly understood. In this study, a novel roseophage, vB_DshS-R26L (R26L), infecting Dinoroseobacter shibae DFL12T, was isolated and characterized in terms of physiological and genomic properties. R26L has siphovirus morphology with an elongated head and a long, non-flexible tail. The phage has a narrow host range and demonstrates a long infection cycle with a latent period of 3.5 h and a burst size of 22 plaque-forming units (PFU cell− 1). R26L possesses a circular, double-stranded DNA genome of 79,534 bp with a G + C content of 62.6%, encoding a total of 116 open reading frames. Notably, seven auxiliary metabolic genes (AMGs), including those related to phosphate metabolism and queuosine biosynthesis, were identified. Phylogenetic and taxonomic analyses revealed that R26L represents a new genus, with its highest intergenomic similarities being 54.7% to another roseophage (R5C). By elucidating the unique characteristics of R26L, this study highlights the complexity of phage infections and the genomic diversity of roseophages, offering valuable insights into the ecological significance of Roseobacter–phage interactions in marine environments.